Clinic management system : ward management system - Nor Zarina, Zamri (2005)
Medical field is very important to human life because it can save a thousand of life but the usage of the clinical management system by using the electronic ways is not very popular among Malaysian. This can be compare to the overseas company that related to the medical stuff have already comfortable with the usage of electronic system. However, the overseas company still not applies the electronic system in all the clinical management phase. Example of the phase that not be discovered yet using this system is the wards department. In Malaysia, this system is not very popular because there is no interest in many of the medical staff to change from the manual system to the electronic system. Some of them think that the new ways can be more difficult compare to the usually ways. Therefore, this thesis proposes the new ways to apply some of the department in the clinical management system which is Ward Management System (WMS). By using these kinds of system all the patient information will be save into database in systematic and efficiently. This also can reduce the lost data problem because all the information will be kept in the database. This system also is not too complicated and easy to understand.